2019
DOI: 10.2478/acph-2020-0012
|View full text |Cite
|
Sign up to set email alerts
|

Self-microemulsifying drug delivery systems of Moringa oleifera extract for enhanced dissolution of kaempferol and quercetin

Abstract: The aim of the present study was to develop self-microemul sifying drug delivery systems (SMEDDS) of the extract of Moringa oleifera, a herbal medicinal plant. Kaempferol and quercetin, the flavonoids present in the leaf extract of M. olei fera, were chosen as markers for quantification. The optimized formulation of SMEDDS consisted of propylene glycol dicaprylocaprate, polysorbate 80, and polyethylene glycol 400 (PEG 400) in a percentage ratio of 20:60:20 (m/m). SMEDDS emulsified immediately (within 20 s) aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
1
6
0
1
Order By: Relevance
“…This indicated that QR-SME possesses a greater surface area, which may promote the rate of quercetin and resveratrol release. Based on particle dispersion, QR-SME presented a unimodal distribution with a very narrow PDI index range, which was lower than that of the resveratrol loading microemulsions [28]; we have previously reported this and confirmed the good dispersion properties of QR-SME. The lower PDI value (< 0.3) indicated the narrow size distribution of the formulation and, furthermore, presented the suitable stability ▶ Table 3 In vivo pharmacokinetic parameters of a self-microemulsifying formulation loaded with quercetin/resveratrol (QR-SME) following oral administration compared with an unformulated quercetin/resveratrol combination (QR suspension) and the combination of Q-SME and R-SME, which represents the SME containing only 40 mg/kg quercetin or resveratrol.…”
Section: Discussionsupporting
confidence: 65%
“…This indicated that QR-SME possesses a greater surface area, which may promote the rate of quercetin and resveratrol release. Based on particle dispersion, QR-SME presented a unimodal distribution with a very narrow PDI index range, which was lower than that of the resveratrol loading microemulsions [28]; we have previously reported this and confirmed the good dispersion properties of QR-SME. The lower PDI value (< 0.3) indicated the narrow size distribution of the formulation and, furthermore, presented the suitable stability ▶ Table 3 In vivo pharmacokinetic parameters of a self-microemulsifying formulation loaded with quercetin/resveratrol (QR-SME) following oral administration compared with an unformulated quercetin/resveratrol combination (QR suspension) and the combination of Q-SME and R-SME, which represents the SME containing only 40 mg/kg quercetin or resveratrol.…”
Section: Discussionsupporting
confidence: 65%
“…Tween 80 and PEG400 are common oral pharmaceutical excipients, and both have very wide oral safety windows. 43 Therefore, EO was selected as the oil phase, Tween 80 as the surfactant, and PEG400 as the cosurfactant.…”
Section: Results and Discussion Preparation And Characterization Of Omentioning
confidence: 99%
“…e estimated absorption of Qu glucoside, the naturally occurring form of Qu, ranges from 3% to 17% in healthy individuals receiving 100 mg [36]. Some modified dosage forms of Qu have been developed to overcome these disadvantages, mainly including nanoparticles [37], microemulsions [38], and other drug carriers [39].…”
Section: Pharmacology and Bioavailability Of Quercetinmentioning
confidence: 99%